Depression and Its Relationship to Self-Concept Among Secondary School Students in the City of Al-Khums (An Empirical Study): Depression and Its Relationship to Self-Concept Among Secondary School Students (Elmergib Journal of Human Sciences, 2026)
This research aims to identify the relationship between depression and self-concept among secondary school students. The research sample consisted of 200 male and female students. The empirical method was used, employing two scales: a depression scale and a self-concept scale. Both scales demonstrated validity and reliability. Statistical methods were used to achieve the research objectives, including split-half testing, t-tests, and linear regression analysis. The research concluded that there were no statistically significant differences in the scores of the sample members on the research scales based on gender. However, there were statistically significant differences in the self-concept scores of the sample members based on their academic specialization, favoring science students. Finally, there were no statistically significant differences in the scores of the sample members on the depression scale .
Keywords: Depression; Self-Concept; Secondary School Students